Peningkatan Pendapatan Pengrajin Batik Mangrove melalui Digital Marketing - Ginting, Riah Ukur; Hasibuan, Renika; Purba, Roberto Roy; Sinaga, Fernando H; Daeli, Yakasi D; Duha, Theresia; Manalu, Anastasia (Universitas Medan Area, 2024)
Mangrove batik artisans in Tanjung Rejo Village, Percut Sei Tuan District, face challenges in increasing their income, primarily due to limitations in production and business management. In production, artisans lack knowledge of design techniques, especially the shibori technique. On the management side, they are underutilizing digital marketing and lack adequate knowledge of computerized financial recording and management. To address these issues, a community partnership empowerment program (PKM) was implemented, aiming to improve the artisans' income through practical training. The training includes: (a) creating fabric patterns using the Shibori technique, (b) utilizing digital marketing, (c) managing business finances using Microsoft Excel, and (d) building a website. The results show significant improvements in digital marketing knowledge, online sales transactions, and the number of social media followers. This training has proven to be an effective solution, enabling mangrove batik artisans to leverage technology to enhance their income.